Firm characteristics, demand for external auditing services and financial performance: an empirical study on cooperative enterprises in East Java, Indonesia / Oyong Lisa, Grahita Chandrarin and Edi Subiyantoro - Oyong, Lisa; Chandrarin, Grahita; Subiyantoro, Edi (Faculty of Accountancy, 2014)
The purpose of this study is to examine the effects of firm characteristics (consisting of members, cooperative scale and liabilities) on the demand for external auditing services and their implications on financial performance. This study uses secondary data collected from the Department of Small and Medium Enterprises and Cooperatives in East Java Province and then analysed using path analysis. Results showed that the effect of firm characteristics consisting only of members and cooperative scale is statistically significant on requests for external audit services. They also showed that the effect of firm characteristics in terms of liabilities and the demand for external auditing services is statistically significant on financial performance, indicating that the number of cooperative members determines the voluntary requests for external audit services. Cooperatives with large numbers of members tend to request for external auditing services. Large-scale cooperatives will increase the volume of transactions, which may cause errors in financial data and statements that will lead to requests for external auditing services. These requests are done to obtain accurate information. The agency theory indicates that cooperation with great amounts of liabilities has to show better performance because activities are monitored by stakeholders. In this case, financial reports are important in forming business decisions.